2018
DOI: 10.1186/s12889-018-5476-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three interventions for secondary prevention of low back pain in the occupational health setting - a randomised controlled trial with a natural course control

Abstract: BackgroundWe assessed the effectiveness of three interventions that were aimed to reduce non-acute low back pain (LBP) related symptoms in the occupational health setting.MethodsBased on a survey (n = 2480; response rate 71%) on LBP, we selected a cohort of 193 employees who reported moderate LBP (Visual Analogue Scale VAS > 34 mm) and fulfilled at least one of the following criteria during the past 12 months: sciatica, recurrence of LBP ≥ 2 times, LBP ≥ 2 weeks, or previous sickness absence. A random sample w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…While determining whether a person is eligible for a prevention program one needs to decide whether such prevention is advisable as well as assess the functional condition of a patient in order to ascertain whether they should seek medical consultation and treatment [13]. When encountering symptoms that may have their source in the spine one may consider consulting with a neurosurgeon [14]. Currently Poland has no standardized and nationwide back pain prevention programs, and Supreme Audit Office has never produced any reports shedding light on prevention of musculoskeletal problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While determining whether a person is eligible for a prevention program one needs to decide whether such prevention is advisable as well as assess the functional condition of a patient in order to ascertain whether they should seek medical consultation and treatment [13]. When encountering symptoms that may have their source in the spine one may consider consulting with a neurosurgeon [14]. Currently Poland has no standardized and nationwide back pain prevention programs, and Supreme Audit Office has never produced any reports shedding light on prevention of musculoskeletal problems.…”
Section: Discussionmentioning
confidence: 99%
“…Back pain prevention comes into question when pain has been experienced recently or has been recurring, radiating to a lower extremity, or causing absenteeism [14]. In order to assess risk factors which, when established, should result in specialist treatment, one should conduct a detailed examination of pain intensity and complete a check for possible "red flags."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that had showed insignificant findings can be summed up by the characteristics of participants, the designed intervention and the event occurred during conducting intervention. One study had included all types of workers that had sickness absence, however, the intervention only focused on improving back pain (Rantonen et al 2018). Furthermore, the intervention conducted on managers involved managers with most experienced in their work and the most senior, which had difficulties to change their behaviour in a short period of time (Stansfeld et al 2015).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Furthermore, the intervention conducted on managers involved managers with most experienced in their work and the most senior, which had difficulties to change their behaviour in a short period of time (Stansfeld et al 2015). The type of intervention also plays an important role as the intervention involving rehabilitation will only have the effect on sickness absence if the intervention is not less than three to four years (Rantonen et al 2018). Furthermore, intervention based on education alone will not give a significant impact on the change of behaviour without the elements of motivation for behaviour change (Stansfeld et al 2015).…”
Section: Quality Assessmentmentioning
confidence: 99%